Project on Human Development in Chicago Neighborhoods (PHDCN): Community Involvement and Collective Efficacy (Primary Caregiver), Wave 3, 2000-2002 - Earls, Felton J. ([Verlag nicht ermittelbar], 2007)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. One such measure was the Community Involvement and Collective Efficacy (Primary Caregiver) instrument. It was administered to subjects' primary caregivers in Cohorts 0, 3, 6, 9, 12, and 15. It collected information relating to participation in community groups, as well as information about the neighborhood. Some of the questions used were drawn from PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS: COMMUNITY SURVEY, 1994-1995 (ICPSR 2766). The same set of questions was administered to subjects in Cohorts 15 and 18 in PROJECT ON HUMAN DEVELOPMENT IN CHICAGO NEIGHBORHOODS (PHDCN): COMMUNITY INVOLVEMENT AND COLLECTIVE EFFICACY (YOUNG ADULT), WAVE 3, 2000-2002 (ICPSR 13686).